Identifikasi Gaya Pengambilan Keputusan Mahasiswa sebagai Konsumen Coffeeshop - Pandu Waso Yustitia; Oki Mardiawan (UNISBA Press, 2022)
Abstract. Previous studies examining consumer decision-making styles in different subjects and contexts have had different results. So that the results of research in the context of coffeeshop consumers will be different from previous research. The amount of coffee consumption in Indonesia continues to increase every year whose consumer dominance is young people, especially students. By making students as young people become the main target in the coffee industry, it becomes important to know their decision-making style. This research aims to get an idea of the decision-making style of students as coffeeshop consumers. The instrument used is the adaptation of Consumer Style Inventory (CSI) into the Indonesian language and the context of coffeeshop consumers. Respondents to this study were college students in the Bandung Raya agglomeration area who had bought / consumed coffee in coffeeshop as many as 211 students (141 women and 70 men) obtained through online questionnaires and determined by purposive sampling techniques. This research design is a descriptive study with categorization analysis techniques, the U Mann-Whitney Test and the Kruskal-Wallis Test. The results of this study found five styles namely Hedonistic, Perfectionism, Confusion from Overchoice, Novelty Consciousness, and Brand Consciousness. Hedonistic style as the most dominating style in students as a consumer of coffeeshop. Abstrak. Penelitian-penelitian sebelumnya yang meneliti gaya pengambilan keputusan konsumen pada subjek dan konteks berbeda didapatkan hasil yang berbeda. Sehingga hasil penelitian pada konteks konsumen coffeeshop akan berbeda dari penelitian sebelumnya. Jumlah konsumsi kopi di Indonesia pun terus meningkat setiap tahunnya yang dominasi konsumennya merupakan orang muda, khususnya mahasiswa. Dengan dijadikannya mahasiswa sebagai orang muda menjadi target utama dalam industri kopi, maka menjadi penting untuk mengetahui gaya pengambilan keputusannya. Penelitian ini bertujuan untuk mendapat gambaran gaya pengambilan keputusan mahasiswa sebagai konsumen coffeeshop. Instrumen yang digunakan adalah adaptasi Consumer Style Inventory (CSI) kedalam bahasa Indonesia dan konteks konsumen coffeeshop. Responden penelitian ini merupakan mahasiswa perguruan tinggi di wilayah aglomerasi Bandung Raya yang pernah membeli/mengkonsumsi kopi di coffeeshop sebanyak 211 mahasiswa (141 perempuan dan 70 laki-laki) yang diperoleh melalui online kuesioner serta ditentukan dengan teknik purposive sampling. Desain Penelitian ini merupakan studi deskriptif dengan teknik analisis kategorisasi, Uji U Mann-Whitney dan Uji Kruskal-Wallis. Hasil pada penelitian ini ditemukan lima gaya yaitu Hedonistic, Perfectionism, Confusion from Overchoice, Novelty Consciousness, dan Brand Consciousness. Dengan gaya Hedonistic sebagai gaya yang paling mendominasi pada mahasiswa sebagai konsumen coffeeshop.